Studies of ternary tin-antimony-selenium-based chalcogenide glasses - Adam, Abdallah Belal (2001)
Tin-antimony-selenium (TAS)-based alloys belong to the ternary chalcogenide compounds of IV-V-VI group, which have been studied for their crystalline structure, however, their amorphous boundary region has not well reported. It is the purpose of this thesis to determine experimentally and theoretically the properties and the boundary of the glass formation region of ternary Sn-Sb-Se systems. Alloy percentages over a wide range of compositions were prepared, in specially designed shaking-furnace and melt-sealing evacuated quartz ampoule using the melt-quenching technique from 700 oC into liquid nitrogen. The characterisation properties including structural, chemical compositions, glass transition, melting and crystallisation temperatures, surface morphology, density and molar-volume, infrared transmission, Raman shift of Sn-Sb-Se systems, were measured. XRD measurements were carried out to identify whether the as-prepared samples were amorphous or crystalline structure and to determine the boundary between the two states. It showed that Sn was incorporated in the ternary systems and formed glass-state up to 12.5- mole percentage. However, crystalline phases such as Sn2Sb4S38 and Sb2Se3, were mostly counted and dominant in crystalline structure samples with Sn-mole percentage more than 12.5. XGT and EDX proved that the samples preserve their theoretical compositions and there was no excessive loss of either chalcogen or the additives. Glass formation region was theoretically validated and mapped when the fraction of Sn-Se bonds is less than 44.5 % or the average co-ordination number is less than or equal 2.4. However, it was experimentally obtained within this region except at excluded areas in the triangle structure. DTA revealed that the glass transition temperature decrcased by increasing Sn-mole percentages and increased by increasing the Sb-mole percentages. As shown in SEM micrographs, addition of a small quantity of Sn and Sb to the glassy Se-based alloy influenced little on the morphology with the kind of the crystallised phases, while markedly observed when a large amount of them was added. The density increased gradually by increasing Snmole percentages, while the molar volume decreased more with Sn than Sb. However, addition of Sn-mole percentage to the systems, showed a new IR-transmission band around 125-145 cm-1, which was assigned to asymmetrical of tetrahedral SnSe4 mode. Raman spectra for pyramidal SbSe3 occurred at 190 cm-1, which was reduced and shifted towards 183 cm-1 when Sn was added to the systems. IR and Raman results confirmed the validity of assuming in amorphous state that 4, 3 and 2 are co-ordination numbers of Sn, Sb and Se, respectively. They were used for proposing the unit structure of the ternary Sn-Sb-Se systems, which was described as a solid solution of Se8 rings with the network structure formed by Se-Sn-Se3-Se-Se-Sb-Se2. Suggestions were made for alternative investigations in future.